2021
DOI: 10.1038/s41467-021-22034-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection induces sustained humoral immune responses in convalescent patients following symptomatic COVID-19

Abstract: Long-term antibody responses and neutralizing activities in response to SARS-CoV-2 infection are not yet clear. Here we quantify immunoglobulin M (IgM) and G (IgG) antibodies recognizing the SARS-CoV-2 receptor-binding domain (RBD) of the spike (S) or the nucleocapsid (N) protein, and neutralizing antibodies during a period of 6 months from COVID-19 disease onset in 349 symptomatic COVID-19 patients who were among the first be infected world-wide. The positivity rate and magnitude of IgM-S and IgG-N responses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
186
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(212 citation statements)
references
References 27 publications
25
186
0
1
Order By: Relevance
“…Monitoring IgG response is an important aspect of understanding the scope of immunity development. There have been previous reports about the persistence of IgG against COVID-19 virus in particular [ 2 , 5 , 7 9 ]. However, the interpretation of such reported studies poses some limitations due to their retrospective nature, short duration, small sample size and lack of repeated quantitative estimation of IgG response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monitoring IgG response is an important aspect of understanding the scope of immunity development. There have been previous reports about the persistence of IgG against COVID-19 virus in particular [ 2 , 5 , 7 9 ]. However, the interpretation of such reported studies poses some limitations due to their retrospective nature, short duration, small sample size and lack of repeated quantitative estimation of IgG response.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Iceland showed the possibilities of a continued antibody response post COVID-19 infections for at least a period of four months [ 9 ]. A study [ 2 ] in Wuhan has investigated the IgG and IgM response in COVID-19 patients for a period of 26 weeks. The study showed IgG positivity rate at about 70% at 6 months follow up period.Another study among 87 American found a decrease in IgG level and memory B cell response consistent with antigen persistence, with a 6 months follow-up [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As was mentioned above, adult acute leukemia patients were capable of developing neutralizing anti-SARS-CoV-2 antibodies [ 2 ]. In our study, the majority of patients demonstrated the presence of anti-spike (anti-RBD) antibodies, which titers appear to closely correlate with the neutralizing capacity [ 4 ]. Moreover, a recent meta-analysis has demonstrated that pediatric patients with COVID-19 suffering from hematological neoplasia or solid tumors were not at an increased risk of unfavorable outcomes [ 5 ].…”
Section: To the Editormentioning
confidence: 99%